Role of postmastectomy radiation therapy after neoadjuvant chemotherapy in locally advanced breast cancer - Akyurek, S.; Yavas, G (Experimental Oncology, 2013)
Neoadjuvant chemotherapy for primary breast cancer is the gold standard in the treatment of locally advanced, inoperable breast cancer, and also based on a large body of evidence has become a standard treatment option for patients with operable disease, who are clear candidates for adjuvant chemotherapy. There are several advantages of administering neoadjuvant chemotherapy: tumor downstaging, improving the chance of breast conserving surgery, in vivo assessment of tumor sensitivity to the chosen therapeutic regimen, and early control of micro-metastatic disease. However there are substantially less data to aid in determining which patients treated with neo-adjuvant chemotherapy warrant postmastectomy radiotherapy. According to the recent literature, patients who require mastectomy after systemic therapy should receive postmastectomy radiotherapy.